Measurement of the cross-section for producing a W boson in association with a single top quark in pp collisions at $ \sqrt{s}=13 $ TeV with ATLAS - ATLAS collaboration (2856 authors) (2018)
The inclusive cross-section for the associated production of a W boson and top quark is measured using data from proton-proton collisions at $ \sqrt{s}=13 $ TeV. The dataset corresponds to an integrated luminosity of 3.2 fb$^{−1}$, and was collected in 2015 by the ATLAS detector at the Large Hadron Collider at CERN. Events are selected requiring two opposite sign isolated leptons and at least one jet, they are separated into signal and control regions based on their jet multiplicity and the number of jets that are identified as containing b hadrons. The W t signal is then separated from the $ t\overline{t} $ background using boosted decision tree discriminants in two regions. The cross-section is extracted by fitting templates to the data distributions, and is measured to be σ$_{W t}$  = 94 ± 10(stat.)$_{− 22}^{+ 28}$ (syst.) ± 2(lumi.) pb. The measured value is in good agreement with the SM prediction of σ$_{theory}$ = 71.7±1.8 (scale)± 3.4 (PDF) pb [1].